Natural and anthropogenic impacts reflected by paleoclimate proxy parameters in a lake-forest system in Bukovina, Romania - Karlik, Máté; Vancsik, Anna; Szalai, Zoltán; Mîndrescu, Marcel; Grădinaru, Ionela; Vágási, Sándor; Bozsó, Gábor; Fekete, József (Hungarian Geographical Bulletin, 2021)
The research area is located in the Eastern Carpathians, Romania. This region is rich in various formations and indicates significant potential for paleo-environmental reconstruction. The present research was carried out on sediment cores collected at lake Bolătău-Feredeu, Feredeului Mountains (Eastern Carpathians, Romania). Preliminary examination of the sediment confirmed the possibility for data analysis with high temporal resolution. The aim of the research was to clarify and supplement the findings of previous research at this site, to explore the relationships between proxy parameters and to elucidate the cause for the changes. Core dating was carried out using 210Pb and radiocarbon isotopes and indicated that sediment cores span the past 500 years. The research uses a wide range of methodologies, including organic geochemistry with calculated n alkane indices (Phw and Pwax). Based on these proxies, the changes of woody and herbaceous coverage in the catchment can be estimated. Moreover, element concentration, weathering indices and particle size distribution assist to detect climate changes in the catchment area. The data and conclusions yielded by the analysis were compared with the regional modelled temperature profile, based on which five periods were separated. In addition to natural and anthropogenic events, the main factor among the natural processes is the change in annual temperature. Based on the obtained data, several parameters were found to be suitable for monitoring past temperature changes.